2020
DOI: 10.1111/ssqu.12883
|View full text |Cite
|
Sign up to set email alerts
|

Are Individuals Harmed by Gerrymandering? Examining Access to Congressional District Offices

Abstract: Objective We consider proximity and access to the district offices of members of Congress to explore whether gerrymandering affects individuals’ capacity to be heard and thus impairs their representation. Methods In a study of six states, we conduct more than 123 million distance measurements to identify residents whose closest district office is in the wrong congressional district. Based on survey results, we then estimate the likelihood that such mismatched individuals will personally visit the office of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Niven then surveyed 1,046 voters from those six states and found that people in mismatched districts were deterred from talking to members of Congress. This is valuable, as it demonstrates another link between individual representation and redistricting (Niven, 2021).…”
Section: Local Effectsmentioning
confidence: 97%
“…Niven then surveyed 1,046 voters from those six states and found that people in mismatched districts were deterred from talking to members of Congress. This is valuable, as it demonstrates another link between individual representation and redistricting (Niven, 2021).…”
Section: Local Effectsmentioning
confidence: 97%
“…The third insight of a traditional literature review is that recent work has continued exploring the effects of gerrymandering on various outcomes including incumbency advantage (Henderson, Hamel, and Goldzimer 2018); electoral competition (Cottrell 2019); candidate quality and emergence (Williamson 2019); roll-call voting and state policy (Caughey, Tausanovitch, and Warshaw 2017); political parties (Stephanopoulos and Warshaw 2020); campaign contributions (Crespin and Edwards 2016); and constituent access (Niven, Cover, and Solimine 2021). Our network also captures these relationships as dyadic connections, but can further illuminate downstream causal chains, confounding concepts, and multiple causal paths.…”
Section: Computersmentioning
confidence: 99%